Separation of the Purpose of Beam Packages with Barcode Based Arduino - Fitriyanto, Febriyan; Mushlihudin, Mushlihudin (Signal and Image Processing Letters, 2020)
In modern times it has experienced a very rapid increase. The industrial world is currently growing and has become an important part. from the world as a whole. Developments in the industrial world today have provided many conveniences and advantages for companies in the process. One example of the use of technology in industry is the process of separating beam packages which is still done manually. If the separation process is still using. Human intervention (manual) will spend a lot of time. In this study, a prototype design of beam package separation that can separate goods automatically with the aim of the zip code already listed in the barcode code, aims to facilitate the performance of beam package separation when. Device design. Hard, namely the Arduino Mega 2560 microcontroller as the command logic storage in the system, two dc motors as conveyor drives, a barcode scanner functions as a barcode code reader, and a servo motor as output. Testing this system uses a package of goods from cardboard media, with a package thickness of 0.2 cm. Based on the results of testing the separation of package beams the tool can work well so that it can increase work effectiveness with an accuracy rate of success of the tool in separating goods packages in each first room with an accuracy of 80% for the purpose of Yogyakarta, then separation of parcels for the purpose of Jakarta with an accuracy of 86.6%, and Separation of beam packages with the destination of goods to Surabaya has an accuracy rate of 86.7%.